2015
DOI: 10.1517/14740338.2015.998197
|View full text |Cite
|
Sign up to set email alerts
|

Labetalol for hypertension in pregnancy

Abstract: Labetalol is a reasonable choice for treatment of severe or non-severe hypertension in pregnancy. However, we should continue our search for other therapeutic options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 60 publications
2
14
0
2
Order By: Relevance
“…Nevertheless, labetalol can attenuate MAP and HR via combined α- and β-receptor blockade (mainly via β-blockade at low dose) without analgesic effect. [19] Ahonen et al [20] reported that beta blockade does not affect SPI values because effects of beta blockade target only the beta receptors of the cardiovascular system, rather than exerting an effect of blunting nociceptive reaction. Furthermore, in this study, labetalol cumulative dose during surgery was small in both groups (median 5 mg, respectively) and it was not significantly different between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, labetalol can attenuate MAP and HR via combined α- and β-receptor blockade (mainly via β-blockade at low dose) without analgesic effect. [19] Ahonen et al [20] reported that beta blockade does not affect SPI values because effects of beta blockade target only the beta receptors of the cardiovascular system, rather than exerting an effect of blunting nociceptive reaction. Furthermore, in this study, labetalol cumulative dose during surgery was small in both groups (median 5 mg, respectively) and it was not significantly different between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Methyldopa is one of the most commonly used anti-hypertensives in pregnancy, but it may also stimulate eryptosis (1231); alternative drugs were considered to be better (1230) for hypertension. Nifedipine (1232) and labetalol (1233) are considered a reasonable choice. There was also a slight reduction in the overall risk of developing proteinuria/PE when beta blockers and calcium channel blockers considered together (but not alone) were compared with methyldopa (1230).…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…Methyldopa is one of the most commonly used anti-hypertensives in pregnancy, but it may also stimulate eryptosis [1158]; alternative drugs were considered to be better [1157] for hypertension. Nifedipine [1159] and labetalol [1160] are considered a reasonable choice. There was also a slight reduction in the overall risk of developing proteinuria/pre-eclampsia when beta blockers and calcium channel blockers considered together (but not alone) were compared with methyldopa [1157].…”
Section: Clotting Coagulopathies and Fibrinogen In Pementioning
confidence: 99%